2022
DOI: 10.1111/tmi.13704
|View full text |Cite
|
Sign up to set email alerts
|

Current status and challenges in the care of patients with bacterial meningitis in the Philippines: A scoping review

Abstract: The Philippines is an archipelago in Southeast Asia (SEA) comprising 7641 islands, which are subdivided into 17 administrative regions [1]. As of 2020, its population is 109.6 million and is ranked as the thirteenth most populous country in the world [2]. The World Bank (WB) categorised the Philippines as a lower middle-income country (LMIC) [3].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Earlier scoping reviews have explored the status and challenges in the care of people with various neurological disorders such as bacterial meningitis, autoimmune encephalitis, brain tumors, epilepsy, multiple sclerosis, and Parkinson's disease in the Philippines [8][9][10][11][12][13], but comprehensive local data on dementia remains lacking. This scoping review aimed to give an overview of dementia care in the Philippines and to identify challenges and gaps in the provision of dementia care in terms of local epidemiology, research, financial coverage, diagnostics, pharmacotherapy, manpower, and caregiver support.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier scoping reviews have explored the status and challenges in the care of people with various neurological disorders such as bacterial meningitis, autoimmune encephalitis, brain tumors, epilepsy, multiple sclerosis, and Parkinson's disease in the Philippines [8][9][10][11][12][13], but comprehensive local data on dementia remains lacking. This scoping review aimed to give an overview of dementia care in the Philippines and to identify challenges and gaps in the provision of dementia care in terms of local epidemiology, research, financial coverage, diagnostics, pharmacotherapy, manpower, and caregiver support.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring treatment gaps for various neurological diseases in the country have shown a want of health information in the form of research. These studies cite a lack of local epidemiologic data and local experience with diagnosis or treatment for autoimmune encephalitis, bacterial meningitis, brain tumors, epilepsy, multiple sclerosis, Parkinson’s disease, and even stroke [ 14 , 15 , 16 , 17 , 18 , 19 ]. By further evaluating research performance, we can identify systemic disparities and guide appropriate solutions and direction for further study.…”
Section: Introductionmentioning
confidence: 99%